Development of an objective tool for the Measurement of Spatial Neglect: A Proof of Concept Study - Auwal Abdullahi; Rukayya Kamal Ibrahim (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2014)
Objective: To determine the concurrent validity, specificity and sensitivity of a newly developed tool; New Neglect Test (NNT) with line bisection test (LBT) and semistructured scale for the functional evaluation of hemi-inattention (SSS) in stroke patients, in assessing spatial neglect. Methods: A total of 28 patients participated in the study. Peripersonal neglect was assessed using LBT and NNT; whereas personal and extrapersonal neglects were assessed using SSS and NNT. Results: The results of the study indicated that the new neglect test has a weak to strong correlation with SSS and LBT at assessing personal, peripersonal and extrapersonal neglect, Phi (Ø) correlation coefficient ranging from r=0.05 to r=-0.66. However, NNT has very low sensitivity and specificity in relation to SSS and LBT when the latter tools are considered as goal standards. Additionally, the result showed that only stage of stroke predicts the NNT's ability to detect spatial neglect in stroke patients, but not age, sex, side affected and MMSE scores. Conclusion: NNT is valid at detecting spatial neglect especially in patients within the acute stage of stroke.